Discrimination of hypoxia tolerant and intolerant hybrid groupers using surface-enhanced Raman spectroscopy of epidermal mucus - Leong, Nathaniel; Mujar, Ellia Kartini; Mazlan, Aini Nadia; Chong, Chou Min; Christianus, Annie; Alresheedi, Mohammed Thamer; Ng, Eng Khoon; Yaacob, Mohd Hanif; Mahdi, Mohd Adzir (Elsevier B.V., 2025)
Fish epidermal mucus contains a wide range of biomolecules and changes in its composition often indicate a response to environmental stressors. Thus, a detailed profile of fish epidermal mucus is crucial to understand its constituents' perturbation when fish is exposed to stressors can offer great insights into its health. Conventional tools to analyse fish epidermal mucus are time-consuming and costly. Meanwhile, surface-enhanced Raman spectroscopy (SERS) coupled with principal component analysis and linear discriminant analysis (PCA-LDA) of epidermal mucus offers a rapid and cost-effective method to elucidate the physiological response to hypoxia in hybrid grouper (Epinephelus fuscoguttatus x Epinephelus lanceolatus). Colloidal SERS was performed on the epidermal mucus immediately after sample collection of fish that were exposed to hypoxia during a power outage. PCA revealed that there was a significant difference in the Raman profile of the mucus after exposure to hypoxia in comparison with the control group. Although the separation of the group that survived the hypoxic event was not very distinct, their physiological responses were less severe. Examination of the PCA loadings showed upregulation of methionine and proteins as indicators of hypoxic stress, particularly in the fish that succumbed to hypoxia. Cystine, phenylalanine and tyrosine concentrations decreased due to the hypoxic stress. However, for the hypoxia-tolerant fish, the decrease was less significant. Using the extracted PCs, a predictive model was constructed using LDA and the model was able to accurately discriminate the susceptible fish from the control group but misclassified a few resilient fishes. Overall, the combination of PCA-LDA indicated that in hypoxia-intolerant fish, a higher degree of stress response was exhibited when exposed to hypoxic condition. The upregulation of methionine and proteins was an indication of hypoxic stress. The downregulation of cystine, phenylalanine and tyrosine showed that a supplement of these amino acids in fish diet may improve the hypoxia tolerance in hybrid groupers.